Ascorbic acid status and aflatoxin production in ripe fruits of jujube infected with Aspergillus flavus - GEETA SUMBALI, YASH PAUL SINGH and (Indian Phytopathology, 2002)
Although eighteen different fungal species caused postharvest decay of jujube (Ziziphus mauritiana) fruits, only Aspergillus flavus infection was of significance. This post-harvest pathogen not only resulted in maximum loss of ascorbic acid from thefruit tissues but also induced aflatoxin production during pathogenesis. It was noted that approximately 85.7% of the A. flavus isolates associated with jujube decay were toxic.